De novo macrolide–glycolipid macrolactone hybrids: Synthesis, structure and antibiotic activity of carbohydrate-fused macrocycles - Desmond, Richard T (Beilstein-Institut, 2014)
Natural product-like macrocycles were designed as potential antibacterial compounds. The macrocycles featured a D-glucose unit fused into a 12- or 13-member macrolactone. The rings are connected via the C6’ and anomeric (C1’) positions of the monosaccharide. The new macrocycles/macrolides were characterized by X-ray crystallography. Their structures showed that, in addition to the ester and alkene units, the dihedral angle about the glycosidic linkage (exo-anomeric effect) influenced the overall shape of the molecules. Glycosylation of an available hydroxy group on the macrocycle gave a hybrid macrolide with features common to erythromycin and sophorlipid macrolactone. Weak antibiotic activity (MICs <100 μg/mL) was observed for several of the compounds.